1993
DOI: 10.1523/jneurosci.13-05-02161.1993
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-releasing hormone (GnRH)-immunoreactive terminal nerve cells have intrinsic rhythmicity and project widely in the brain

Abstract: Modulation of ionic channel properties and synaptic functions by neurotransmitters and hormones is called neuro-modulation and may be the basis for many long-lasting changes in animal behavior, for example, changes in the arousal or motivational states. We have previously shown in a teleost, the dwarf gourami, that the terminal nerve (TN) cells are a major component of the gonadotropin-releasing hormone (GnRH) system and are structurally independent from the preoptic/hypophysial-GnRH system, which projects to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
139
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(153 citation statements)
references
References 67 publications
13
139
1
Order By: Relevance
“…However, the present results also indicate a minor contribution of sGnRH fibers to the pituitary, although the precise origin of these projections remains to be established. In the dwarf gourami, the terminal nerve ganglion cells have been shown to project widely in the brain, but not in the pituitary (Oka & Matsushima 1993). It is generally believed that GnRH-immunoreactive cells of the terminal nerve are not essential for the regulation of gonadotropin release, an assumption strongly reinforced by the fact that sectioning the olfactory tract in female goldfish does not impair gonadal development and ovulation (Kobayashi et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…However, the present results also indicate a minor contribution of sGnRH fibers to the pituitary, although the precise origin of these projections remains to be established. In the dwarf gourami, the terminal nerve ganglion cells have been shown to project widely in the brain, but not in the pituitary (Oka & Matsushima 1993). It is generally believed that GnRH-immunoreactive cells of the terminal nerve are not essential for the regulation of gonadotropin release, an assumption strongly reinforced by the fact that sectioning the olfactory tract in female goldfish does not impair gonadal development and ovulation (Kobayashi et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…So far, it has been suggested that TNGnRH neurons show regular pacemaker activities (Fujita et al 1991;Oka and Matsushima 1993;Ramakrishnan and Wayne 2009;Wayne et al 2005) and GnRH release is evoked by depolarizing stimulus that increases the firing frequency of these neurons (Abe and Oka 2007;Ishizaki et al 2004). Considering that TN cell bodies appear to receive direct and indirect inputs from multimodal sensory systems (Fujita et al 1985(Fujita et al , 1991Ramakrishnan and Wayne 2009; Ito 2000), GnRH should be released from TN depending on these sensory inputs.…”
Section: The Significance Of the Modulatory Effect Of Gnrh On The Olfmentioning
confidence: 99%
“…There are some reports that GnRH has neuromodulatory effects on the sensory responsiveness of animals (Abe and Oka 2007;Eisthen et al 2000;Kawai et al 2009b;Oka 1997;Oka and Matsushima 1993;Park and Eisthen 2003;Umino and Dowling 1991). In mudpuppies (Necturus maculosus), for example, GnRH increases the amplitude of a tetrodotoxinsensitive inward current in the olfactory receptor neurons (Eisthen et al 2000), suggesting that GnRH increases the excitability of these neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Despite large decreases in the brain sGnRH contents, gonadal maturation was not inhibited (Kobayashi et al , 1994Kim et al 2001). In dwarf gourami, sGnRH neurons in the TN may be the most extensively projecting GnRH neurons in the brain except in the pituitary (Oka and Matsushima 1993). These results indicate that most of the sGnRH fibers in the brain originates from the TN and that sGnRH neurons in the TN do not project to the pituitary.…”
Section: -1 Changes In Gnrh Peptide Levels During Gonadal Maturatiomentioning
confidence: 80%